PEMANFAATAN WEBSITE PEMERINTAH KOTA PEKANBARU DALAM MEWUJUDKAN GOOD GOVERNANCE - Yohana, Nova; Yazid, Tantri Puspita (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
Pekanbaru governmentâs website with domain www.pekanbaru.go.id is one of strategy to improve e-Government to achieve good governance. The purpose of this research is to know the benefit, efficiency, participation, transparency and change management of using website as the implementation of information and communication technology to achieve Good Governance on Pekanbaru government. This research used qualitative method with Balanced E-Government Scorecard Theory. The data collected from observation, interview and documentation. The result shows that using Pekanbaru governmentâs website as interactive public services to give information to the people is not maximized yet. The efficiency of using the website as public information is not running well. But it can help data electronic administrator and people to work. Participation as two way communication still runs slowly at menuâCall usâ and âGive your aspirationâ. The transparency of websiteâs use still have pro and contra between people and the management to give information clearly. ChangeManagement byusing website in tightly controlling and monitoring with E-Government system still not running well. The use of Pekanbaru governmentâs website still not able to achieve Good Governance yet. High commitment supported from mayor as the district head and all level of bureaucracy are needed to arrange system and process of public information services via Pekanbaru governmentâs website.